Reprocessable polyurethane elastomers based on reversible ketal exchange: dielectric properties and water resistance. Issue 4 (5th January 2023) - Dong, Jianrong; Yan, Hongye; Lv, Xinhai; Wang, Zhenbang; Rao, Zixuan; Zhu, Bailin; Wu, Jun; Zhou, Yu; Chen, Hongxiang
Abstract : The ketal-containing cross-linked polyurethane elastomer exhibits reprocessability and excellent dielectric properties. In addition, it shows good water resistance. Abstract : Polyurethane elastomers (PUEs) not only have high intrinsic dielectric constants, but also possess repeated deformation ability due to their crosslinking structure, so the conventional cross-linked PUE is often used as a dielectric elastomer. However, cross-linked PUEs cannot be reprocessed or heal as this will lower their use efficiency. Although the introduction of dynamic covalent bonds can solve this problem, it is a great challenge to design dynamic covalent cross-linked PUEs with excellent dielectric properties. Based on this consideration, ketal with two hydroxyl groups obtained by the reaction of 2, 5-hexanedione and glycerol is used as a chain extender to prepare ketal-containing dynamic covalent cross-linked PUE. Cyclic ketal contains polar C–O bonds, and its asymmetric structure can weaken the interactions between hard segments in polyurethane, which enhance the orientation of polar groups, thus improving the dielectric properties. Moreover, the ketal-containing cross-linked PUE is capable of self-healing, reshaping, and reprocessing owing to the reversible heat exchange of ketal. Thus, the ketal-containing PUE exhibits reprocessability and excellent dielectric properties (a dielectric constant of 11.9 and a dielectric loss factor of 0.045 at 10 3 Hz). In addition, the ketal-containing cross-linked PUE has better water resistance. This study provides a way to obtain dynamic covalent cross-linked PUEs with excellent dielectric properties.